Differences in Pharyngeal Characteristics According to Angle Class of Malocclusion - Diamantidou A.; Topouzelis N.; Sidiropoulou-Hadjigianni S.; Gkantidis N. (Balkan Stomatological Society, 2015)
Objectives: To investigate potential differences in the pharynx, the soft palate, the pharyngeal tonsil, and the tongue between patients with different Angle Classes of malocclusion.